Analysis of Job Satisfaction and Work Environment on Employee Turnover Intention - Cedaryana, C.; Safria, Dhuha (Manunggal Halim Jaya, 2025)
High turnover rates can lead to losses for a company. The turnover phenomenon begins with turnover intention, which is influenced by several factors, including job satisfaction and work environment. This study quantitatively analyzes the influence of job satisfaction and work environment on employee turnover intention at PT. XYZ. Involving 62 respondents and using multiple linear regression analysis, the study results show that both job satisfaction and work environment, partially and simultaneously, have a positive and significant effect on employee turnover intention. The R-square calculation result is 0.225, which means that the job satisfaction and work environment variables collectively explain 25.5% of the variance in turnover intention among PT. XYZ employees. The remaining variance can be explained by other variables beyond the scope of this study.